Legal Protection for Victims of Sexual Violence Categorized as Disabled (Decision Number 59/Pid.B/2024/PN.Mbn) - Ismayanti, Eli; Gagarin Akbar, Muhammad Gary; Abas, Muhamad (Dinasti Research, 2025)
The incidents of sexual violence against individuals with intellectual disabilities highlights how the legal system should play a more comprehensive role in providing protection, particularly in terms of restitution US part of victim recovery. This study aims to examine the legal protection mechanisms for victims of sexual violence based on existing legislation and to analyze its implementation for individual with intellectual disabilities, US reflected in Decision No. 59/Pid.B/2024/PN. Mbn. Using normative juridical methods and a case law approach, this research evaluates the consistency between legal norms and judicial practice. The findings indicate that although the regulations mandate restitution, in this case, it was note granted due to the absence of a formal request from the victim, despite the fact that the victim, as an individual with an intellectual disability, requires a more active legal protection mechanism. This gap underscores the need for reform in judicial approaches, where judges should proactively determine restitution without relying on victim petitions, alongside enhanced coordination between law enforcement authorities and social institutions to ensure that victims receive comprehensive legal protection, including psychological and social recovery